2020
DOI: 10.3389/ffgc.2020.543112
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Soil Responses to Nitrogen and Phosphorus Fertilization Along a Soil Phosphorus Stock Gradient

Abstract: In this study, we investigate the responses of soil organic carbon (C) to nitrogen (N) and phosphorus (P) additions along a soil P stock gradient of five beech forest stands in Germany, using a modeling approach. Two different soil models with coupled C, N, and P cycles are used to simulate fertilization experiments conducted at the study sites. The first model, the stand-alone soil module of QUINCY (QUINCY-soil, Thum et al., 2019), is a conventional soil model that uses first-order kinetics to describe soil o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…3). The model performance in simulating the relationship between soil labile and sorbed Pi pools (Lab-to-Exchangeable P) has been improved by dbLang at our study sites of varying soil P stocks, soil texture, and stoichiometry (Lang et al, 2017;Yu et al, 2020b). Such an improvement of dbLang with respect to reproducing the Lab-to-Exchangeable P ratio much better captures the vertical patterns of soil inorganic pools (Figs.…”
Section: Model Representation Of Soil Pi Cycling and Langmuir Sorptionmentioning
confidence: 84%
See 1 more Smart Citation
“…3). The model performance in simulating the relationship between soil labile and sorbed Pi pools (Lab-to-Exchangeable P) has been improved by dbLang at our study sites of varying soil P stocks, soil texture, and stoichiometry (Lang et al, 2017;Yu et al, 2020b). Such an improvement of dbLang with respect to reproducing the Lab-to-Exchangeable P ratio much better captures the vertical patterns of soil inorganic pools (Figs.…”
Section: Model Representation Of Soil Pi Cycling and Langmuir Sorptionmentioning
confidence: 84%
“…In the Mann-Kendall test, the tau (τ ) value varies between −1 and 1, where −1 represents a decreasing trend and 1 repre-sents an increasing trend. The modeled soil profile against the measured soil profile was evaluated with a normalized rootmean-square ratio term, K nrmsr , which is modified to represent the average proportions between modeled and measured values (Yu et al, 2020b).…”
Section: Model Evaluationmentioning
confidence: 99%
“…Another avenue forward is studying the effect of stoichiometric constraints by other elements than C and N. The next step is to include phosphorus (P) constraints. A first implementation in the JSM model (Yu et al, 2020b) revealed several challenges.…”
Section: Discussionmentioning
confidence: 99%
“…There are several different ways to represent N limitation effects in land models, including using N to scale down photosynthesis (Ghimire et al, 2016;Goll et al, 2017;Thum et al, 2019;Yu et al, 2020;Zaehle et al, 2015;Zhu et al, 2019), scaling down potential GPP based on N availability (Gerber et al, 2010;Oleson et al, 2013;Wang et al, 2010), or defining an NPP cost of nitrogen uptake (Fisher et al, 2010). We choose the most physiological way by adjusting maximum Rubisco carboxylation rate (𝑉 !,789 ) during the photosynthesis process, rather than adjusting NPP at the end of the photosynthesis process.…”
Section: Effect Of Nitrogen Limitation On Photosynthesis Based On Soi...mentioning
confidence: 99%